Preparation method of ion-type rare earth ore standard substance and application thereof
Patent Information
- Application Number
- CN202611069107.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-17
AI Technical Summary
[0008]本发明的目的在于提供一种离子型稀土矿标准物质制备方法及其应用,解决现有制备工艺适配能力差、矿样结构易破坏、标准物质均匀性和稳定性不足的技术问题
[0018]1、本发明采用变压呼吸式循环干燥工艺,替代传统高温烘干工艺,通过负压抽湿、常压静置、正压定型的周期性呼吸式干燥,可在常温低损伤状态下彻底脱除矿样水分,有效避免矿样吸潮、结块,精准控制含水率在3~5%,同时保护离子型稀土的原有赋存结构,避免活性离子流失。
Smart Images

Figure CN122567343B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of rare earth mineral standard material preparation technology, and more specifically, it relates to a method for preparing ionic rare earth mineral standard materials and their application. Background Technology
[0002] Ion-adsorption rare earth minerals are a unique mineral resource in my country, and their standard reference materials are core reference materials for rare earth ore testing, quality assessment, and scientific research experiments. my country's ion-adsorption rare earth minerals are mostly distributed in the southern regions, where the mining areas have high humidity and high air moisture content. Traditional methods for preparing rare earth ore standard reference materials often employ rigid processing techniques such as high-temperature drying, vigorous mechanical grinding, and static sieving. Currently, the industry's conventional preparation process for ion-adsorption rare earth ore standard reference materials mainly uses traditional methods such as natural air drying, manual assisted crushing, static sieving, and short-term uniform mechanical mixing.
[0003] However, traditional preparation processes have the following problems:
[0004] (1) High-temperature drying can easily lead to the loss of active ions on the surface of rare earth minerals and sintering of mineral sample structure, thus destroying the occurrence morphology of ion-type rare earths.
[0005] (2) Strong mechanical grinding will cause excessive crushing and damage to the mineral lattice, resulting in rare earth element segregation and reducing the uniformity of standard materials;
[0006] (3) Conventional static drying cannot be adapted to high humidity environment, the mineral sample is not dried thoroughly, the moisture content fluctuates greatly, and it is very easy to absorb moisture and clump;
[0007] (4) Traditional mixing methods have low mixing efficiency and poor uniformity. The final standard substances prepared have problems such as poor stability, substandard uniformity, and easy deterioration under high humidity conditions, which cannot meet the requirements of high-precision rare earth detection, mineral reserve assessment, and scientific research experiments. Summary of the Invention
[0008] The purpose of this invention is to provide a method for preparing ionic rare earth mineral standard materials and its application, thereby solving the technical problems of poor adaptability of existing preparation processes, easy damage to mineral sample structure, and insufficient uniformity and stability of standard materials.
[0009] To achieve the above objectives, the present invention adopts the following technical solution:
[0010] A method for preparing ionic rare earth mineral standard reference materials includes the following steps:
[0011] S1: Pressure Swing Breathing Drying: The collected ion-adsorption rare earth ore samples are placed in a sealed drying chamber and a cyclic drying procedure of "negative pressure dehumidification, normal pressure standing, and positive pressure shaping" is performed until the sample moisture content drops to 3-5%;
[0012] The specific parameters for the pressure-switching breathing dryer are as follows: during the negative pressure dehumidification stage, the vacuum degree is controlled at -0.08MPa to -0.04MPa, and the duration is 2 to 4 hours; during the positive pressure setting stage, dry air or nitrogen is introduced, and the pressure is controlled at 0.02MPa to 0.05MPa, and the duration is 1 to 2 hours; the total number of drying cycles is 3 to 5.
[0013] S2: Flexible shear dissociation: The dried sample is fed into a planetary differential mixer to perform low-energy dissociation, and the particle size distribution of the dissociated sample is controlled to be 0.25~0.5mm; the shear force field intensity of the planetary differential mixer is controlled to be 50~80 N / m²; the revolution speed of the planetary differential mixer is 100~150 r / min, the rotation speed is 200~250 r / min, and the revolution and rotation directions are opposite.
[0014] S3: Gradient electrostatic screening: Using the principle of electrostatic separation, the sample processed in step S2 is passed through a high-voltage electrostatic field to separate ultrafine dust. The electrostatic separation voltage is set to 20~30 kV.
[0015] S4: Tilting and mixing: Place the coarse particle component screened in step S3 into a tilting mixing device, control the rotation speed to 40~60 r / min, and the mixing time to 48~72 hours, so that the relative standard deviation (RSD%) of the characteristic quantities between and within the standard material units is less than 5%.
[0016] Furthermore, the method is applied to the large-scale production of ion-type rare earth mineral standard materials, with a single batch processing capacity of 50 kg to 500 kg.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. This invention adopts a pressure-switching breathing cycle drying process to replace the traditional high-temperature drying process. Through the periodic breathing drying of negative pressure dehumidification, normal pressure standing, and positive pressure shaping, the moisture of the mineral sample can be completely removed under normal temperature and low damage conditions, effectively avoiding moisture absorption and agglomeration of the mineral sample, accurately controlling the moisture content at 3~5%, and protecting the original occurrence structure of ion-type rare earth and avoiding the loss of active ions.
[0019] 2. This invention uses planetary differential reverse rotation to achieve low-energy flexible shearing dissociation. By precisely controlling the shear force field intensity and rotation speed parameters, uniform dissociation of the mineral sample is achieved, avoiding excessive crushing and lattice damage. The particle size is precisely controlled to be stable at 0.25~0.5mm, ensuring the integrity of the mineral particle structure.
[0020] 3. This invention removes ultrafine dust and micro-impurities generated during the preparation process through high-pressure gradient electrostatic screening, eliminates elemental segregation caused by micro-particle agglomeration, and improves the purity and particle size consistency of the mineral sample.
[0021] 4. This invention, combined with a long-lasting low-speed tumbling mixing process, achieves all-round mixing of mineral samples without dead corners, greatly improving the uniformity of standard materials, making the relative standard deviation (RSD%) of characteristic quantities consistently less than 5%. The prepared standard materials have strong stability and high detection accuracy under high humidity conditions and can be used for long-term rare earth mineral detection and calibration. Attached Figure Description
[0022] Figure 1 This is a schematic diagram of the preparation process of this method. Detailed Implementation
[0023] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments, control experiments and corresponding test data.
[0024] Experimental materials: In-situ raw ore samples were taken from the ion-adsorption rare earth mining area in southern Jiangxi. The initial moisture content was 18-22%, and the total rare earth content ΣREO was 0.12-0.15%. The samples showed no obvious weathering, mold, or impurity contamination.
[0025] Experimental equipment: sealed variable pressure drying chamber, planetary differential speed mixer, high voltage electrostatic separator, flip-type sample mixer, moisture analyzer, laser particle size analyzer, inductively coupled plasma mass spectrometer (ICP-MS), electronic analytical balance, constant temperature and humidity test chamber (simulating a high humidity environment, humidity 65%±5%, temperature 25℃±2℃).
[0026] Core testing indicators and corresponding standards
[0027] (1) Sample moisture content: The final moisture content was precisely controlled to be 3-5% according to GB / T 10322.5-2024 Determination of moisture content in iron ore delivery lot;
[0028] (2) Particle size distribution: According to GB / T 10322.1-2014 Determination of moisture and particle size of iron ore, the target particle size is 0.25~0.5mm (60 mesh), and the particle size qualification rate is ≥98%;
[0029] (3) Relative standard deviation of homogeneity (RSD%): According to the "JJF 1005-2016 General Terms and Definitions for Standard Materials", 20 sets of parallel samples were randomly selected to detect the total rare earth content, and the RSD% was calculated. The requirement is that RSD% < 5%;
[0030] (4) High humidity stability: The prepared standard material was placed in an environment with 65% humidity and 25℃ for 30 days. The change in moisture content and RSD% was detected. No obvious moisture absorption and no significant fluctuation in uniformity were considered qualified.
[0031] (5) Dust removal rate: In accordance with the GB / T 6003 test sieve standard, the samples before and after screening were screened using a 0.075mm standard sieve. The dust removal rate was calculated by weighing the mass retained by each sieve layer, with a target removal rate of ≥95%.
[0032] All experimental groups and comparative samples used the same batch of ion-adsorption rare earth ore, underwent uniform pretreatment to remove macroscopic impurities such as stones and plant roots, and were sampled at a uniform amount of 5 kg. The preparation process was strictly carried out in accordance with the corresponding process parameters. Three parallel experiments were set up for all test items, and the average value was taken as the final test data.
[0033] Example 1
[0034] A method for preparing ionic rare earth mineral standard reference materials, the specific preparation steps are as follows:
[0035] S1: Pressure Swing Breathing Drying: 5 kg of pretreated rare earth ore was placed in a sealed drying chamber, and a cyclic drying program was executed; during the negative pressure dehumidification stage, the vacuum degree was -0.06 MPa for 3 hours; the sample was then left to stand at normal pressure for 10 minutes; during the positive pressure shaping stage, drying nitrogen gas was introduced at a pressure of 0.03 MPa for 1.5 hours; the total duration of a single cycle was 4.67 hours, and 4 cycles were executed consecutively. The precise moisture content of the dried sample was 4.20%.
[0036] S2: Flexible shear dissociation: The dried sample was fed into a planetary differential speed mixer, with the revolution speed set to 120 r / min and the rotation speed set to 220 r / min, with the revolution and rotation in opposite directions. The shear force field intensity was controlled at 65 N / m², and the low-energy dissociation treatment was carried out for 20 min. After dissociation, the proportion of particles with a size of 0.25~0.5 mm in the sample was 99.20%.
[0037] S3: Gradient electrostatic screening: Set the electrostatic separation voltage to 25kV, perform electrostatic separation on the dissociated sample, and thoroughly separate ultrafine dust and micro-impurities;
[0038] S4: Tilting and mixing: The qualified coarse particle components after screening are fed into a tilting mixing device, and the rotation speed is 50 r / min. The mixture is continuously mixed for 60 h to obtain the final ion-type rare earth mineral standard material.
[0039] The test data for this embodiment are as follows: 1. Sample moisture content: 4.20%; 2. Particle size qualification rate: 99.20%, with no over-crushed particles or large particle residues, and uniform particle size distribution; 3. Ultrafine dust removal rate: 98.52%; 4. Uniformity RSD%: 2.18%; 5. High humidity stability (30d, 65%RH, 25℃): moisture content fluctuation 0.30%, RSD% fluctuation 0.25%, the sample showed no moisture absorption, clumping, elemental segregation, or component deterioration, and exhibited excellent stability.
[0040] Example 2
[0041] A method for preparing ionic rare earth mineral standard reference materials, the specific preparation steps are as follows:
[0042] S1: Pressure swing drying: negative pressure dehumidification vacuum degree -0.08MPa, lasting 4 hours; positive pressure shaping by introducing dry air at a pressure of 0.05MPa, lasting 2 hours; 5 drying cycles were performed continuously, and the precise moisture content of the dried sample was 3.12%;
[0043] S2: Flexible shear dissociation: revolution speed 150r / min, rotation speed 250r / min, reverse rotation, shear force field strength 80N / m², dissociation treatment 15min;
[0044] S3: Gradient electrostatic screening: Separation voltage 30kV to complete the separation of dust and impurities;
[0045] S4: Mix by inversion: Mix continuously at 60 r / min for 72 h to prepare the standard substance.
[0046] The test data for this embodiment are as follows: 1. Sample moisture content: 3.12%; 2. Particle size qualification rate: 98.73%; 3. Ultrafine dust removal rate: 97.81%; 4. Uniformity RSD%: 2.85%; 5. High humidity stability (30d, 65%RH, 25℃): moisture content fluctuated by 0.40%, RSD% fluctuated by 0.31%, and there were no abnormal changes in sample morphology and composition.
[0047] Example 3
[0048] A method for preparing ionic rare earth mineral standard reference materials, the specific preparation steps are as follows:
[0049] S1: Pressure swing breathing drying: negative pressure dehumidification vacuum degree -0.04MPa, lasting for 2 hours; positive pressure shaping by introducing drying nitrogen gas at a pressure of 0.02MPa, lasting for 1 hour; three drying cycles were performed continuously, and the precise moisture content of the dried sample was 4.78%;
[0050] S2: Flexible shear dissociation: revolution speed 100r / min, rotation speed 200r / min, reverse rotation, shear force field strength 50N / m², dissociation treatment 25min;
[0051] S3: Gradient electrostatic screening: 20kV sorting voltage to remove ultrafine dust;
[0052] S4: Mix by turning: Mix continuously at 40 r / min for 48 h to prepare the standard substance.
[0053] The test data for this embodiment are as follows: 1. Sample moisture content: 4.78%; 2. Particle size qualification rate: 98.15%; 3. Ultrafine dust removal rate: 96.24%; 4. Uniformity RSD%: 3.42%; 5. High humidity stability (30d, 65%RH, 25℃): Moisture content fluctuation 0.50%, RSD% fluctuation 0.38%, no component segregation, moisture absorption and deterioration problems, meeting the requirements for use in high humidity environments.
[0054] To further demonstrate the technical superiority of each set of embodiments, the existing optimal conventional preparation process under the corresponding operating conditions is matched as an independent comparative example.
[0055] Comparative Example 1
[0056] It adopts conventional commercial preparation process in southern mining areas: natural sun drying, manual crushing, 18-mesh sieve, short-term 24-hour mixing at 60r / min, without pressure change drying, without flexible dissociation, and without electrostatic impurity removal, which is suitable for conventional preparation conditions.
[0057] Test data: Sample moisture content 5.96% (exceeding the standard); particle size qualification rate 83.26%; ultrafine dust residue rate 12.35%; uniformity RSD%=6.93%; moisture content increase of 1.85% after 30 days of high humidity, with obvious local rare earth segregation.
[0058] Compared to the existing optimal traditional process, the moisture content of Example 1 of this invention is reduced by 1.76%, the particle size qualification rate is increased by 15.94%, the RSD% is significantly reduced by 4.75%, and the high humidity stability is significantly improved. Its comprehensive performance surpasses that of the existing technology.
[0059] Comparative Example 2
[0060] Comparative Example 2 uses a traditional high-intensity processing technology: hot air drying, high-speed high-intensity grinding, high-pressure sieving, and short-time mixing, which is the existing high-intensity preparation solution in the industry.
[0061] Test data: rare earth active ion loss rate 7.85%; particle size qualification rate 80.12%; uniformity RSD%=7.21%; easily absorbs moisture and deteriorates under high humidity environment, and the matrix structure is severely damaged.
[0062] While existing high-strength rigid processes improve crushing efficiency, they severely damage the mineral sample matrix and active components, resulting in homogeneity and stability far inferior to the upper limit parameter scheme of Example 2 of this invention. This demonstrates that the upper limit parameter of this invention has the unique advantages of low damage and high homogeneity.
[0063] Comparative Example 3
[0064] Comparative Example 3 uses a traditional light-treatment preparation process: natural air drying, slight crushing, and low-speed short-time mixing, which is a conventional low-damage solution.
[0065] Test data: Moisture content 5.82% (exceeding the standard); poor particle size uniformity, with coarse and fine particles mixed; dust removal rate 0%; uniformity RSD% = 6.15%, which cannot meet the requirements for large-scale preparation.
[0066] Existing traditional light treatment processes cannot simultaneously achieve water control, impurity removal, and homogenization, but the process of this invention can still fully meet the standards under the lower limit of parameters.
[0067] To fully verify the technical superiority of the core process parameters and process combinations of this invention, and to distinguish it from the shortcomings of conventional existing technologies, this invention demonstrates, through multi-dimensional comparisons including deviations of single parameters, simultaneous deviations of multiple parameters, missing core processes, and parameter values outside the specified range, that the process parameter ranges, process combinations, and equipment matching relationships defined by this invention cannot be easily obtained through conventional experiments. All experimental examples were conducted with the same basic conditions, sampling quantities, and testing standards as Example 1, with only corresponding variables changed.
[0068] Experimental Example 1
[0069] The difference between this Experimental Example 1 and Example 1 is that step S1, pressure swing drying, is omitted, and traditional high-temperature drying in an oven is used. The drying temperature is 105℃ and the drying time is 8 hours. The remaining process parameters S2, S3, and S4 are completely consistent with those of Example 1.
[0070] Test data: The moisture content of the sample after drying was 3.85%, and the mineral sample showed obvious micropore sintering and pore closure; the particle size qualification rate was 82.26%; the dust removal rate was 98.20%; the uniformity RSD% was 7.62% (significantly exceeding the standard); after 30 days of high humidity, the moisture content rose to 9.52%, and large-area moisture absorption and agglomeration occurred, the total loss rate of rare earth active ions was 8.73%, and the original structure of the matrix was destroyed.
[0071] Traditional high-temperature drying processes cannot be adapted to high-humidity preparation conditions, and will irreversibly damage the original structure of rare earth minerals, resulting in loss of active components and excessive uniformity.
[0072] Experiment Example 2
[0073] The difference between this Experimental Example 2 and Example 1 is that step S2, reverse differential flexible dissociation, is replaced with traditional forward mechanical grinding, and the shear force field strength is increased to 120 N / m². The remaining process parameters are completely consistent with those of Example 1.
[0074] Test data: Sample moisture content 4.20%; particle size qualification rate 75.58%, over-crushed particles (<0.25mm) accounted for 22.84%; dust removal rate 90.08%; uniformity RSD%=6.85% (significantly exceeding the standard); after 30 days of high humidity, RSD% fluctuated by 1.22%, with severe stratification of light and heavy particles, and the local segregation coefficient of rare earth elements exceeded 30%.
[0075] Exceeding the shear force field defined by this invention and canceling the reverse differential flexible dissociation mode will cause excessive crushing of mineral particles, lattice damage, and severe element segregation.
[0076] Experimental Example 3
[0077] The difference between this experimental example 3 and example 1 is that step S3, the gradient electrostatic screening process, is deleted, and the sample directly enters the mixing process after dissociation. The remaining process parameters are completely consistent with those of example 1.
[0078] Test data: Sample moisture content 4.20%; particle size qualification rate 85.17%; ultrafine dust removal rate 0%; residual amount of fine dust <0.075mm 14.83%; uniformity RSD%=5.93% (exceeding the standard); after 30 days of high humidity, fine dust agglomerated and clumped over a large area, and the extreme deviation of local rare earth detection reached 28.6%, resulting in the failure of sample consistency.
[0079] Without a high-voltage gradient electrostatic screening process, fine dust remains and causes high-humidity agglomeration and segregation, failing to meet the metrological requirements of standard substances. This demonstrates the necessity and inventiveness of the electrostatic impurity removal process of this invention.
[0080] Experiment Example 4
[0081] The difference between this experimental example 4 and example 1 is that the mixing parameters in step S4 are adjusted to a rotation speed of 80 r / min and a mixing time of 24 h, both of which are outside the 40~60 r / min and 48~72 h range specified in this invention. The remaining process parameters are completely consistent with those in example 1.
[0082] Test data: Sample moisture content 4.20%; particle size qualification rate 99.01%; dust removal rate 98.30%; uniformity RSD%=5.26% (slightly exceeding the standard); the sample has obvious coarse and fine particle stratification, and the maximum deviation of rare earth characteristic quantity between units is 6.32%, which cannot meet the uniformity threshold requirements of the standard material.
[0083] If the parameters deviate from the long-term low-speed mixing parameter range of this invention, problems such as sample stratification and excessive homogeneity may occur.
[0084] Experimental Example 5
[0085] The difference between Example 5 and Example 1 is as follows: S1: negative pressure vacuum degree -0.03MPa, 2 cycles; S2: shear force field 90N / m², positive rotation grinding; the remaining parameters S3 and S4 are the same as those in Example 1.
[0086] Test data: Sample moisture content 6.85% (exceeding the standard); particle size qualification rate 81.33%; uniformity RSD%=8.12%; moisture content increase after 30 days of high humidity 2.15%; sample slightly caking.
[0087] The core drying and dissociation parameters deviated from the range defined in this invention, resulting in process synergy failure and excessive moisture content and uniformity. This proves that the parameter range of this invention has strict coupling and is not a conventional choice.
[0088] Experimental Example 6
[0089] The difference between this experimental example 6 and example 1 is that: S3: electrostatic separation voltage 15kV; S4: rotation speed 70r / min, mixing time 36h; the other parameters S1 and S2 are the same as those in example 1.
[0090] Test data: Ultrafine dust removal rate 82.16%; uniformity RSD%=7.35%; rare earth characteristic quantity deviation between units 7.81%; dust agglomeration was obvious after high humidity placement, and the quantity stability was poor.
[0091] When the impurity removal parameters and the mixing parameters deviate in tandem, the combined defects of residual impurities and uneven mixing lead to a significant deterioration in product quality.
[0092] Experimental Example 7
[0093] Compared with Example 1, Example 7 differs in the following ways: S1: High-temperature drying replaces pressure swing drying; S2: Positive high-intensity grinding and high-force field crushing; S3: Electrostatic screening is cancelled; only S4 conventional mixing is retained.
[0094] Test data: rare earth active ion loss rate 9.12%; particle size qualification rate 70.25%; uniformity RSD%=9.86%; complete agglomeration after 30 days of high humidity, and the measurement value is completely invalid.
[0095] When multiple core processes are replaced with existing conventional technologies, the products completely fail to meet the standards for the preparation of standard substances.
[0096] As demonstrated by the above embodiments, comparative examples, and experimental cases, in the environment of southern mining areas, high levels of water vapor in the air are easily adsorbed onto the porous surface of rare earth minerals. Traditional static drying can only remove free water from the surface of the mineral sample, making it difficult to completely remove bound water inside the pores. Furthermore, the dried mineral sample is highly susceptible to reverse moisture absorption. This invention employs a breathing-like circulation mechanism of "negative pressure dehumidification, normal pressure static placement, and positive pressure shaping." During the negative pressure stage, free water vapor and interstitial air within the pores of the mineral sample are rapidly extracted, disrupting the moisture adsorption balance. During the normal pressure static placement stage, moisture within the pores of the mineral sample slowly migrates outward, preventing mineral particle cracking caused by rapid dehydration. The introduction of drying gas under positive pressure replaces residual humid air within the pores, compacting the loose structure of the mineral sample and sealing the water absorption channels in the pores.
[0097] Through 3 to 5 cycles, the moisture content can be precisely controlled at 3 to 5% under normal temperature and low damage conditions. This not only completely removes internal moisture but also preserves the complete pore structure of the mineral sample, significantly improving the sample's resistance to moisture absorption. This addresses the root causes of moisture absorption, clumping, and large fluctuations in moisture content in mineral samples under high humidity conditions, while avoiding defects such as thermal decomposition of rare earth ions and loss of activity caused by high-temperature drying.
[0098] Secondly, rare earth elements in ionic rare earths exist in an adsorbed state on the surface and pores of mineral particles. Traditional high-intensity grinding, which mainly relies on impact and extrusion crushing, easily damages the crystal structure of mineral particles, leading to the shedding and loss of adsorbed rare earth ions, while also generating a large amount of ultrafine debris, causing elemental segregation. This invention employs planetary differential motion with opposite revolution and rotation, combined with a low shear force field of 50~80 N / m², replacing high-intensity impact crushing with flexible shearing and kneading action.
[0099] The reverse differential speed operation of the equipment creates a multi-dimensional flexible force field inside the cavity, which only breaks up the agglomerates of the mineral sample without destroying the crystal structure and rare earth occurrence morphology of the individual mineral particles. It can accurately control the particle size of the mineral sample within a uniform range of 0.25~0.5mm, which not only solves the problems of raw ore agglomeration and uneven particle size, but also preserves the original physicochemical properties of rare earth minerals to the greatest extent, ensuring the authenticity of the matrix of the standard material.
[0100] During the flexible dissociation process, a small amount of ultrafine dust debris is generated. These fine particles have a large specific surface area and strong adsorption capacity, making them prone to agglomeration in high-humidity environments. This results in localized high rare earth content and decreased overall uniformity of the standard material. This invention utilizes the difference in charge of mineral particles of different sizes. In a 20-30kV high-voltage electrostatic field, ultrafine dust and qualified coarse particles exhibit differentiated migration motion: the ultrafine dust has a high charge density and fast migration speed, and is adsorbed and collected by the electric field, while qualified large particles are subjected to uniform force and fall steadily.
[0101] This process can remove ultrafine dust and micro-impurities without damage and with high efficiency, without changing the physicochemical properties of qualified mineral particles. It effectively eliminates elemental segregation caused by micro-particle agglomeration, further improves the particle size consistency and component purity of mineral samples, and lays the foundation for subsequent high-precision mixing.
[0102] Traditional short-time, high-speed mixing methods are prone to problems such as mineral sample stratification and uneven local mixing, failing to meet the requirement of uniform distribution of trace components in standard materials. This invention employs a low-speed, long-term tumbling mixing mode of 40~60 r / min, with a long mixing time of 48~72 h, which can achieve dynamic displacement mixing of mineral samples in all directions without dead corners. The low-speed condition avoids the stratification of coarse and fine particles caused by high-speed centrifugation.
[0103] Through long-term continuous turning, mixing, and homogenization, mineral particle components from different locations and batches are fully integrated, achieving uniform distribution of rare earth characteristic quantities within and between units. Ultimately, the relative standard deviation (RSD%) is controlled within 5%, ensuring that the prepared standard material has high precision and good repeatability, and can be used as a reference material for high-precision detection and calibration.
[0104] In this invention, pressure swing breathing drying solves the problems of water control stability and moisture resistance of mineral samples under high humidity conditions; flexible shearing and dissociation achieve non-destructive and uniform granulation, preserving the original characteristics of the mineral samples; electrostatic screening removes fine impurities and eliminates the risk of segregation; and long-term tumbling mixing achieves high-precision homogenization. These four processes form a complete flexible preparation system, avoiding the defects of traditional rigid processes such as structural damage, poor uniformity, and weak adaptability to high humidity. Ultimately, it produces ion-adsorption rare earth mineral standard materials that are suitable for high humidity environments, have excellent stability, and meet the homogeneity standards.
[0105] Example 4
[0106] This embodiment provides a method for the large-scale preparation of ionic rare earth mineral standard materials, with a single batch processing capacity of 200 kg. The specific steps are as follows:
[0107] S1: Pressure Swing Breathing Drying: 200 kg of the collected ion-adsorption rare earth ore sample was placed in a sealed drying chamber with an effective volume of 2 m³, and a cyclic drying procedure of "negative pressure dehumidification, normal pressure settling, and positive pressure setting" was executed. During the negative pressure dehumidification stage, the vacuum degree was controlled at -0.06 MPa and dehumidification was continued for 3 hours; then, it was set at normal pressure for 30 minutes; during the positive pressure setting stage, dry air was introduced, and the pressure was controlled at 0.03 MPa for 1.5 hours. This constitutes one cycle, and a total of 4 cycles were performed. After drying, samples were taken for testing. The sample moisture content dropped to 3.8%, and the relative standard deviation (RSD%) of the moisture content at each sampling point was less than 3%, indicating good drying uniformity.
[0108] S2: Flexible Shear Dissociation: 200 kg of dried sample was fed into a planetary differential mixer with an effective volume of 0.5 m³ for low-energy dissociation. The operating parameters were: revolution speed 120 r / min, rotation speed 220 r / min, revolution and rotation directions opposite, shear force intensity controlled at 65 N / m², and processing time 40 minutes. After dissociation, samples were taken for particle size analysis. The results showed that over 92% of the sample particles were between 0.25 and 0.5 mm (i.e., 60 mesh), meeting the particle size requirements for subsequent electrostatic screening.
[0109] S3: Gradient Electrostatic Screening: The dissociated sample is subjected to gradient electrostatic screening through a high-voltage electrostatic field, with the electrostatic separation voltage set to 25 kV. Under the action of the voltage gradient, ultrafine dust (particle size <0.25 mm) is effectively separated and collected. Testing showed that the content of dust with a particle size <0.25 mm in the separated coarse particle component (approximately 195 kg) was reduced to below 1.5%, effectively avoiding interference from ultrafine dust on the homogeneity of the standard material.
[0110] S4: Tilting and Mixing: The coarse particle component (approximately 195 kg) after electrostatic screening was placed into a tilting mixing device with an effective volume of 1.5 m³. The rotation speed was controlled at 50 r / min, and the mixing time was 96 hours. During the mixing process, the device was paused every 24 hours for sampling and testing to monitor the progress of mixing uniformity. After mixing, 10 samples were collected from different positions on the device (top, middle, bottom, and four corners) to determine the total amount of rare earth elements in the ionic phase. The test results showed that the relative standard deviation (RSD%) of the characteristic quantities among the samples was 3.2%–4.5%, all less than 5%, meeting the homogeneity requirements between and within the standard material units.
[0111] The method described in this embodiment enables the large-scale production of ion-adsorption rare earth mineral standard materials (single batch processing capacity of 200 kg, which can be stably expanded to the range of 50 kg to 500 kg). The obtained standard materials have good homogeneity and can meet the actual needs of ion adsorption rare earth resource exploration and evaluation.
[0112] The embodiments of the present invention are given for illustrative and descriptive purposes only, and are not intended to be exhaustive or to limit the invention to the forms disclosed. Many modifications and variations will be apparent to those skilled in the art. The embodiments were chosen and described in order to better illustrate the principles and practical application of the invention, and to enable those skilled in the art to understand the invention and to design various embodiments with various modifications suitable for a particular purpose.
Claims
1. A method for preparing ionic rare earth mineral standard references, characterized in that, Includes the following steps: S1: Pressure Swing Breathing Drying: The collected ion-adsorption rare earth ore samples are placed in a sealed drying chamber and a cyclic drying procedure of "negative pressure dehumidification, normal pressure standing, and positive pressure shaping" is performed until the sample moisture content drops to 3-5%; S2: Flexible shear dissociation: The dried sample is fed into a planetary differential speed mixer to perform low-energy dissociation on the sample, and the particle size distribution of the dissociated sample is controlled to be 0.25~0.5mm; the shear force field intensity of the planetary differential speed mixer is controlled to be 50~80 N / m². S3: Gradient electrostatic screening: Using the principle of electrostatic separation, the sample processed in step S2 is passed through a high-voltage electrostatic field to separate ultrafine dust impurities. The specific parameters for the "pressure swing drying" in step S1 are as follows: during the negative pressure dehumidification stage, the vacuum degree is controlled at -0.08MPa to -0.04MPa, and the duration is 2 to 4 hours; during the positive pressure setting stage, dry air or nitrogen is introduced, and the pressure is controlled at 0.02MPa to 0.05MPa, and the duration is 1 to 2 hours; the total number of drying cycles is 3 to 5. The operating parameters of the planetary differential mixer in step S2 are: revolution speed of 100~150 r / min, rotation speed of 200~250 r / min, and the revolution and rotation directions are opposite. In step S3, the voltage for electrostatic separation is set to 20~30 kV.
2. The method for preparing an ionic rare earth mineral standard substance according to claim 1, characterized in that, The particle size distribution of the sample after dissociation in step S2 is 60 mesh.
3. The method for preparing an ionic rare earth mineral standard substance according to claim 1, characterized in that, It also includes step S4: inverting and mixing: the coarse particle component screened in step S3 is placed into an inverting mixing device, the rotation speed is controlled at 40~60 r / min, the mixing time is 48~72 hours, so that the relative standard deviation (RSD%) of the characteristic quantities between and within the standard material units is less than 5%.
4. A method for preparing ionic rare earth mineral standard material according to any one of claims 1 to 3, characterized in that, The method is applied to the large-scale production of ion-type rare earth mineral standard materials, with a single batch processing capacity of 50 kg to 500 kg.
Citation Information
Patent Citations
Method and device for manufacturing dispersed mineral products
CN101203317A
Ion-absorbed rare earth mine ion phase standard material and preparation method thereof
CN105890956A
Anhydrous magnesium nitrate and preparation method thereof
CN116002729A
Planetary differential efficient stirring device
CN202592532U